WTO ministerial conferences : key outcomes / World Trade Organization. (Cambridge University Press, 2023)
WTO Ministerial Conferences: Key Outcomes contains all the key outcomes from World Trade Organization Ministerial Conferences since the organization was established in 1995. Covering 12 Ministerial Conferences held between 1996 and 2022, the key outcomes include Ministerial Decisions and Declarations as well as Chairpersons' statements. This publication also reproduces relevant ministerial outcomes of the Uruguay Round adopted in connection with the establishment of the WTO that were not formally integrated into the Marrakesh Agreement Establishing the WTO. This publication complements The WTO Agreements, published by Cambridge University Press and the WTO, which contains the Marrakesh Agreement Establishing the WTO and its Annexes.